Cost Estimation for Engineering Work by Co-operation of Visual Basic, Auto CAD and Microsoft Excel - Suksing, Uthai; Kreankard, Santi; Promme, Witool (Engineering and Applied Science Research, 2013)
At present, it is quite complicated to calculate the costs of engineering work, as it requires accuracy and efficiency. There are a lot of software programs in the world market. However, their prices and copyrights are expensive and they can not meet with a local user’s requirement. This project studies the development of new software for estimation for engineering work by the co-operation of the currently used software: Visual Basic, Auto CAD and Microsoft Excel. Visual Basic is used to read data from Auto CAD program while Auto CAD is used to count and operate block layers of equipment and items of the engineering work. Microsoft Excel is used for calculating and presenting the result in the final report. This program also allows users to edit and change as well as up-date. The development has show that this program can reduce time used for cost estimation. Accuracy and simplicity are also considered major advantages.